Peningkatan Pengetahuan Masyarakat tentang Program Keluarga Berencana - Lestari, Dwi; Lieskusumastuti, Anita Dewi; Sari, Wina Junita (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
The Family Planning (KB) Program is one of the government's main strategies in controlling population growth and improving the quality of life of the community. However, uneven knowledge among the community often becomes an obstacle in the implementation of this program. This community service activity aims to increase community knowledge about the KB program. The activity was carried out in May 2024 in Mojosongo Village, Jebres, Surakarta, with participants consisting of fertile couples, cadres, and mothers of toddlers. The methods used included interactive counseling and group discussions. The results showed a significant increase in knowledge in participants, measured through pre-tests and post-tests. It is hoped that this increase in knowledge will encourage active community participation in the KB program and the implementation of recommended practices, which will ultimately also improve maternal and child health.